2008
DOI: 10.1161/strokeaha.107.505313
|View full text |Cite
|
Sign up to set email alerts
|

Think to Move: a Neuromagnetic Brain-Computer Interface (BCI) System for Chronic Stroke

Abstract: Background and Purpose-Stroke is a leading cause of long-term motor disability among adults. Present rehabilitative interventions are largely unsuccessful in improving the most severe cases of motor impairment, particularly in relation to hand function. Here we tested the hypothesis that patients experiencing hand plegia as a result of a single, unilateral subcortical, cortical or mixed stroke occurring at least 1 year previously, could be trained to operate a mechanical hand orthosis through a brain-computer … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
476
1
7

Year Published

2013
2013
2018
2018

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 548 publications
(497 citation statements)
references
References 32 publications
13
476
1
7
Order By: Relevance
“…Features from a set of sensors, such as the power at a frequency window or the level of activation, can be classified as multivariate patterns of activity (MVPAs). The calculated signal is then presented to the individual via visual, auditory 72 , haptic 139 or electrical stimulation 210 feedback, allowing the user to alter neural function and complete the loop with neural processing of feedback. The advantages and disadvantages of these modalities, as well as how their signals are processed for neurofeedback, are discussed in BOX 1.…”
Section: Coherencementioning
confidence: 99%
See 1 more Smart Citation
“…Features from a set of sensors, such as the power at a frequency window or the level of activation, can be classified as multivariate patterns of activity (MVPAs). The calculated signal is then presented to the individual via visual, auditory 72 , haptic 139 or electrical stimulation 210 feedback, allowing the user to alter neural function and complete the loop with neural processing of feedback. The advantages and disadvantages of these modalities, as well as how their signals are processed for neurofeedback, are discussed in BOX 1.…”
Section: Coherencementioning
confidence: 99%
“…Active patient participation in the therapy is another guiding principle of rehabilitation that is derived from studies employing forced use of the affected limb 137 and robotic therapy that minimizes assistance to encourage greater patient effort 138 . One promising avenue for stroke rehabilitation involves exoskeletal training that uses real-time signals from sensorimotor areas 139 .…”
Section: Rehabilitation In Strokementioning
confidence: 99%
“…This option receives further credence in findings coming from stroke patients, who manifest impaired muscular control and take much longer-13 to 22 sessions of one-to-two hours-to govern the MEG signal (Buch et al, 2008). Moreover, with one exception (Gallegos-Ayala et al, 2014), patients lacking control of all muscles (e.g., completely locked-in patients) have been entirely unsuccessful in maintaining control over neuroimaging signals (De Massari et al, 2013).…”
Section: Megmentioning
confidence: 99%
“…In a typical trial, the detection of movement intention would trigger a contingent sensory feedback to the user. This feedback can be delivered in an abstract form (e.g., a moving cursor on a computer screen) or as embodied feedback (e.g., visual representations of the participant's body parts over a virtual avatar on a computer screen, in a VR head‐mounted display or directly overlaid on the participant's limbs; or somatosensory representations delivered through robotic, haptic or Neuromuscular Electrical Stimulation (NMES) systems) that reproduces the intended movement, which was shown to enhance motor learning 19, 20, 21…”
Section: Introductionmentioning
confidence: 99%
“…showed that severely paralyzed chronic stroke patients could learn to control their ipsilesional SMR 21. Since then, an international effort has taken place to investigate whether repeated BCI training can lead to motor recovery.…”
Section: Introductionmentioning
confidence: 99%